2014
DOI: 10.1002/2013jd021040
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal variation of aerosol properties from Indo‐Gangetic Plain to central Himalayan foothills during TIGERZ campaign

Abstract: As part of TIGERZ campaign, latitudinal variation of aerosol optical properties was analyzed over Indo-Gangetic Plains (IGP) to central Himalayas during premonsoon of 2008 and 2009. Measurements of aerosol optical depth (AOD) were performed using Aerosol Robotic Network Sun photometer at four sites with different aerosol environments. The AOD increases from Nainital located in central Himalayas to Kanpur located in IGP region. Further, aerosol size varies spatially with dominance of coarse-mode aerosols at Kan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 77 publications
(195 reference statements)
2
21
0
Order By: Relevance
“…Moreover, the standard tropical atmospheric profiles of pressure, temperature and relative humidity (RH) were used along with daily ozone (267e280 DU) and surface reflectance (0.13e0.20) obtained from Aura Ozone Monitoring Instrument (OMI) version 3 reflectivity data, while the WVC (1.5e3.5 mg m À3 ) was obtained from daily Terra-MODIS observations (level 3, C005.1). On the other hand, the EC radiative effect was estimated via a similar technique by using the SBDART retrievals with and without daily EC concentrations Srivastava et al, 2012;Dumka et al, 2013Dumka et al, , 2014Bisht et al, 2015). In this procedure, the basic input parameters were the AOD, SSA and g. The SSA and g for EC were estimated via OPAC in two steps, (i) including and (ii) excluding the water-soluble and insoluble aerosol components.…”
Section: Estimation Of Darementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the standard tropical atmospheric profiles of pressure, temperature and relative humidity (RH) were used along with daily ozone (267e280 DU) and surface reflectance (0.13e0.20) obtained from Aura Ozone Monitoring Instrument (OMI) version 3 reflectivity data, while the WVC (1.5e3.5 mg m À3 ) was obtained from daily Terra-MODIS observations (level 3, C005.1). On the other hand, the EC radiative effect was estimated via a similar technique by using the SBDART retrievals with and without daily EC concentrations Srivastava et al, 2012;Dumka et al, 2013Dumka et al, , 2014Bisht et al, 2015). In this procedure, the basic input parameters were the AOD, SSA and g. The SSA and g for EC were estimated via OPAC in two steps, (i) including and (ii) excluding the water-soluble and insoluble aerosol components.…”
Section: Estimation Of Darementioning
confidence: 99%
“…The vertical distributions of aerosols and clouds are critical for the magnitude or even the sign of DARE (Chand et al, 2009;Dumka et al, 2014). Kaskaoutis et al (2013) estimated the vertical radiative forcing and heating rates over Kanpur using the measured lidar profiles, but only for composite aerosols, while Srivastava and Ramachandran (2013) provided different profiles of heating rates for various aerosol mixing (external and internal) scenarios over central IGP.…”
Section: Estimation Of Darementioning
confidence: 99%
“…In summary, the variation in AOD with latitude is reproduced well by all three categories, though there are numerical differences, which get larger over the north of IGB. Dumka et al (2014) have re-cently shown the latitudinal variation in aerosol properties over the IGB based on ground-based remote-sensing data from AERONET. They observed an increase in AOD from the central Himalayas to IGB.…”
Section: Cmip5mentioning
confidence: 99%
“…In this respect, Srivastava et al (2011a) reported ARF values of À45, À30, and +15W m À2 at surface, TOA and atmosphere, respectively and heating rate of $0.4 K/day during dusty days over Nainital. During the pre-monsoon seasons of and 2009, Dumka et al (2014 calculated ARF values at Nainital in the order of À45.7, À7.6 and 38.1 W m À2 at surface, TOA and atmosphere, respectively, with heating rate of 1.07 K/day. The radiative perturbation due to dust aerosols averaged over the region (25-30°N and 70-80°E) were À8.0 ± 3.3 W m À2 at surface, À2.9 ± 3.1 W m À2 at TOA and 5.1 ± 3.3 W m À2 in the atmosphere , with severe instantaneous surface cooling of À227 W m À2 and large À70 W m À2 instantaneous ARF at TOA during the dust event of 20 April 2010.…”
Section: Aerosol Radiative Forcing During Major Dust Stormsmentioning
confidence: 99%
“…Except of local-regional factors, like soil moisture, surface winds, convection, the dust activity over the Indian sub-continent was found to be associated with synoptic meteorology and weather systems (Das et al, in press-b; Kaskaoutis et al, in press-b) as well as with the intensity of the monsoonal circulation and rainfall (Rahul et al, 2008;Vinoj et al, in press). Study of dust activity over northern India has significant importance during the pre-monsoon season, because of the aerosol mixture with the background pollution levels that enhances the aerosol loading (Kumar et al, 2012) and associated effects in radiative forcing, atmospheric heating, monsoon circulation and rainfall distribution (Gautam et al, 2009b(Gautam et al, , 2011Srivastava et al, 2010;Giles et al, 2011;Das et al, 2013;Dumka et al, 2014). In this respect, Dey et al (2004) and El-Askary et al (2006) have focused on certain dust storms in the IGB region, while studied dust storms during a long-term period (2001)(2002)(2003)(2004)(2005) using ground and satellite data.…”
Section: Introductionmentioning
confidence: 99%